The Next Frontier of Regulatory T Cells: Promising Immunotherapy for Autoimmune Diseases and Organ Transplantations - Terry, Lauren V.; Oo, Ye Htun (Frontiers in Immunology, 2020)
Abstract: Regulatory T cells (Tregs) are crucial in maintaining tolerance. Hence, Treg immunotherapy is an attractive therapeutic option in autoimmune diseases and organ transplantations. Currently, autoimmune diseases do not have a curative treatment and transplant recipients require to take life-long immunosuppression to prevent graft rejection. There has been significant progress in understanding of polyclonal and antigen-specific Treg biology over the last decade. Clinical trials with good manufacturing practice (GMP) Treg cells have demonstrated safety and early efficacy of Tregs therapy. GMP Treg cells can also be tracked following infusion. In order to improve efficacy of Tregs immunotherapy, it is necessary that Tregs migrate, survive and function at the specific target tissue. Application of antigen specific Treg cells and maintaining cells’ suppressive function and survival with low dose interleukin -2 (IL-2) will enhance the efficacy and longevity of infused GMP-grade Tregs. Notably, stability of Treg cells in the local tissue can be manipulated by understanding the microenvironment. With the recent advances in GMP-grade Tregs isolation and antigen-specific chimeric antigen receptor (CAR)-Tregs development will allow functionally superior cells to migrate to the target organ. Thus, Tregs immunotherapy may be a promising option for patients with autoimmune diseases and organ transplantations in near future. Contribution to the field This review summarizes the overview and progress of Tregs applications in autoimmune diseases and organ transplantation. We describe the role of Tregs, and discuss the current application in the clinical settings. We believe that our review makes a significant contribution to understanding the role of Tregs in autoimmune diseases and transplantations both are important in clinical and research areas. Current treatment options for both conditions is very limited and patients require to take life-long immunosuppressive medications. We believe that this paper will be of interest to the readership of Frontiers Journal as it summarizes the available overview knowledge of Tregs cells application linking Treg biology and its application as early phase clinical trials in human autoimmune diseases and transplantations.